2021
DOI: 10.2166/ws.2021.396
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on monthly water consumption on a tropical tourism island: case study of Phuket (Thailand)

Abstract: Phuket is a tropical island in Thailand that is famous for tourism. The COVID-19 pandemic resulted in the number of tourists reducing to almost zero. Since tourism contributes around one-half of the gross provincial product of Phuket, the impact was so severe that even the numbers of people employed and registered as locals decreased. Analysing the data from January 2015 to March 2021, we found that the total, residential and non-residential monthly consumptions dropped significantly after Thailand's State of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Water demand patterns radically changed with the pandemic; household consumption increased all over the world [4][5][6][107][108][109], while industrial and public (universities, colleges, schools, administrative buildings, hotels, etc.) sectors encountered a significant drop in consumption due to their temporary or permanent closures [110,111]. Therefore, the studies are focused on the problems that may occur in the water system infrastructure [112] due to the changes in water demand.…”
Section: Access To Safe and Improved Drinking Watermentioning
confidence: 99%
“…Water demand patterns radically changed with the pandemic; household consumption increased all over the world [4][5][6][107][108][109], while industrial and public (universities, colleges, schools, administrative buildings, hotels, etc.) sectors encountered a significant drop in consumption due to their temporary or permanent closures [110,111]. Therefore, the studies are focused on the problems that may occur in the water system infrastructure [112] due to the changes in water demand.…”
Section: Access To Safe and Improved Drinking Watermentioning
confidence: 99%
“…This may be due to its complex geographical setting characterized by mountainous and surrounded by the Andaman Sea, leading to hot temperatures and humidity throughout the year. 67 When considering in the context of the health impact levels classified by NWS, it was found that more than 60% of HI in Maha Sarakham Province, Chaiyaphum Province, and Phuket Province were in the extreme caution and higher health-impact classes (Figure 6). However, the HI with the danger level was greater than 1 5%.…”
Section: Pilot Areas Testedmentioning
confidence: 99%